Monitoring the modifications of Aloe vera by high performance liquid chromatography - Tojeira, Ana (2019)
Aloe vera is a widely known and studied plant due to its therapeutic properties. The therapeutic properties exhibited by the Aloe vera exudates have been associated to the presence of certain compounds, such as, chromones, anthrones and anthraquinones. In this study, we have identified, and monitored by reversed phase high performance liquid chromatography (HPLC), six major compounds present in the Aloe vera exudates. The chromatographic profiles were followed in the course of time and at different wavelengths. This monitoring allowed us to verify the constitution and modifications of the samples, in order to identify the main changes responsible for the chemical degradation and loss of proprieties exhibited by the exudates over time.